The crisis of Arab culture and intellectuals, according to Burhan Ghalioun - Said Karoui (Social Empowerment Journal, 2021)
The study of the term culture and the Arab intellectual is one of the pioneering topics that researchers in the field of contemporary Arab thought have addressed, as they are considered one of the foundations in building societies, stabilizing their existence and imposing their hegemony within the world. It has become imperative for learners to study intellectuals and culture, and to write in this field to define the methods and mechanisms guaranteeing the success of the project of renewing Arab culture, and then achieving the Arab civilization renaissance.From this standpoint, Burhan Ghalioun dealt with the Arab culture and intellectual, and explained the role entrusted to him, highlighting the solutions that would move the intellectual from a stage of stagnation to a phase of action and dynamism, and he dealt with the importance of culture in consolidating the building values ​​for the advancement of society in general and individuals in particular, and clarified the relationship between the fundamentalist intellectual and the modernist one.